Implementasi Nilai-nilai tasawuf Akhlaqi Menghadapi fenomena punic buying - Sidiq Rahmadi (Hikamia: Jurnal Pemikiran Tasawuf dan Peradaban Islam, 2024)
Abstract The COVID-19 pandemic has hit the world, causing price increases and increased public demand. The result is that punic buying behavior appears. The aim of this research is to determine the implementation of Akhlaqi Sufism values ​​in responding to the punic buying phenomenon. This research is literature research. This research uses primary and secondary data. This research investigates the principles of Sufism that may have an impact on the psychological problems faced by society today. Data was collected by searching relevant literature on the subject. Then, the data is classified according to the problem discussed, followed by analysis and interpretation of the data according to the principle of sufficiency. Analysis and interpretation are presented using a descriptive approach. The results of this research are that the behavior of hoarding goods due to concerns about price fluctuations is known as punic buying. According to Akhlaqi Sufism, buying sinful goods is behavior that can harm other people. Hoarding is a logical action taken by people who feel threatened and limited. In akhlaqi Sufism, actions that harm other people are considered bad behavior that originates from lust. To anticipate such actions, individuals must be aware of their needs, the study found. Keywords: Covid, Morals, Panic Buying, Sufism. Abstrak Pandemi COVID-19 melanda dunia, menyebabkan kenaikan harga dan peningkatan permintaan masyarakat. Akibatnya adalah muncul perilaku punic buying. Adapun tujuan penelitian ini adalah mengetahui Implementasi Nilai-nilai tasawuf Akhlaqi Menyikapi fenomena punic buying. Penelitian ini adalah penelitian literatur, Penelitian ini menggunakan data primer dan sekunder. Penelitian ini menyelidiki prinsip-prinsip tasawuf yang mungkin berdampak pada masalah kejiwaan yang dihadapi masyarakat saat ini. Data dikumpulkan dengan mencari literatur yang relevan tentang subjek tersebut. Kemudian, data diklasifikasikan sesuai dengan masalah yang dibahas, diikuti oleh analisis dan interpretasi data sesuai dengan prinsip secukupnya. Analisis dan interpretasi disajikan menggunakan pendekatan deskriptif.. Hasil penelitian ini adalah Perilaku menimbun barang karena kekhawatiran tentang fluktuasi harga dikenal sebagai buying punic. Menurut tasawuf akhlaqi, membeli barang berdosa adalah perilaku yang dapat merugikan orang lain. Penimbunan barang adalah tindakan logis yang dilakukan oleh orang-orang yang merasa terancam dan terbatas. Secara tasawuf akhlaqi, perbuatan yang merugikan orang lain dianggap sebagai perilaku buruk yang berasal dari nafsu. Untuk mengantisipasi tindakan tersebut, individu harus sadar akan kebutuhannya, menurut temuan penelitian ini. Kata Kunci: Covid, Punic Buying, Tasawuf,Akhlaqi.